ANALISIS PENGARUH DIMENSI CASH CONVERSION CYCLE TERHADAP RETURN ON ASSET (Studi Pada Perusahaan Food and Beverages Yang Tercatat Di Bursa Efek Indonesia Periode Tahun 2010 - 2012) - Ulfi Amalia; Khanifah khanifah (Universitas Wahid Hasyim, 2015)
This study aimed to examine the effect of dimensional analysis of the cash conversioncycle Return on Assets (ROA) (studies on food and beverages companies listed in IndonesiaStock Exchange (IDX) year period from 2010 to 2012). The independent variable in this studyused the inventory conversion period, receivables collection period, and the period ofsuspension of debt, control variables in this study were the current ratio, laverage, and size,and the dependent variable in this study is ROA. This study used purposive sampling methodin determining the number of samples used and acquired 20 companies were used as samples.This study uses regression analysis using the classical assumption pand using the softwareSPSS 17.00. The test results obtained with SPSS for the variable X1 (Inventory ConversionPeriod) that the inventory conversion period negative effect on ROA obtained t value = -6.588with a significance level of 0.000. The test results obtained with SPSS for the variable X2(Receivables Collection Period) that the Accounts receivable collection periods negativelyaffect ROA obtained t value = -9.761 with a significance level of 0.000. The test resultsobtained with SPSS for variable X3 (Debt Suspension Period) that the Debt deferral periodhas positive effect on ROA obtained t value = 3.949 with a significance level of 0.000. The testresults obtained with SPSS for the variable X4 (Current Ratio) while the current ratio has apositive effect on ROA obtained t value of 2.571 with a significance level of 0.014. The testresults obtained with SPSS for the variable X5 (Laverage) that the laverage negative effect onROA obtained t value of -11.681 with a significance level of 0.000. The test results obtainedwith SPSS for variable X6 (Size) that the size has a positive effect on ROA obtained t value of231.693 with a significance level of 0.000.Keywords : Conversion Period Inventory, Accounts Receivable Collection Period,Suspension Period payable, Current Ratio, Laverage, Size.